Reconstitution of the Core Ccr4-Not Complex and Evidence for Possible Interaction between YTHDF2 and Human CNOT9 - Gong, Yutong (2025)
In eukaryotic cells, shortening and removal of the poly(A) tail of cytoplasmic mRNA (deadenylation) is a key step in mRNA degradation. Studies have shown that the Ccr4-Not complex plays a fundamental role in regulating gene expression at the posttranscriptional level. The different parts of this complex are connected by flexible linkers, which act like bridges to hold the structure together and enable it to work properly. However, it’s currently unclear whether these linkers have preferred conformations or have considerable flexibility. To purify and generate different sub-complexes of Ccr4-Not for biochemical and structural investigation, and further investigate the remodeling and structural dynamics of the Ccr4-Not complex, we focused on purifying and analyzing two important subcomplexes of the core Ccr4-Not complex: the Nuclease/CNOT9 module and the Nuclease/CNOT9/NOT module. I demonstrated the practicality and efficiency of the strategy of co-expressing protein complexes and purifying proteins using Immobilised metal affinity chromatography (IMAC). Secondly, I investigated recruitment of Ccr4-Not complex by YTHDF2 RNA binding protein via CNOT9, since YTHDF2 protein plays a central role in the degradation of m6A-modified mRNA, which is mainly achieved through interaction with the Ccr4-Not complex. In order to explore the interaction between CNOT9 and YTHDF2 domain and further figure out the mechanistic basis of mRNA degradation mediated by YTHDF2 through the Ccr4-Not complex, I demonstrated through peptide pull-down experiments that human CNOT9 can interact with YTHDF2.